History of Medicine, Medicalisation and Strategies of Historical Knowledge - Liepoldová, Tereza (Dějiny – teorie – kritika, 2025)
The study examines the development of the history of medicine from its beginnings to the present, exploring key transformations and methodological influences that have shaped the field. It focuses on two main areas. The first involves the concepts and intellectual "turns" that have influenced historical medical research, including medicalisation, the cultural and linguistic turn, new materialism, the turn to emotions, and the neurosciences – known as neurohistory. The second area analyses how historical reflection has led to the transformation of approaches in medicine, particularly in psychiatry, where debates on treating mental illness have emerged. The article demonstrates how these changes not only reshaped historical knowledge but also influenced medical practice and theory. It aims to deepen the understanding of the connections between history, society, and medicine, while also presenting the new challenges faced by historians of medicine in contemporary research.